HUBUNGAN SIKAP SOSIAL DAN SPIRITUAL DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DIKELAS XI IPS SMAN 1 KOTO XI TARUSAN - vera haslinda; Ernawati Ernawati (JURUSAN GEOGRAFI FIS UNP, 2020)
The purpose of this research is to see whether or not there is a relationship between social and spiritual attitudes and learning outcomes. This research is the population is all students at XI IPS SMAN 1 Koto XI Tarusan totaling 130 people. The technique of determining the sample in this study was purpose sampling, namely class XI IPS 2 SMAN 1 Koto XI Tarusan, which amounted to 31 students, the reason the researcher took purpose sampling was because it had a special characteristic that was the same as the research objectives such as knowing the social and spiritual attitudes of students, data collection techniques. used in this research are observation, questionnaire data collection tools, correlation data analysis techniques. The results showed that: (1) the social attitude of the students got as much as 84%, meaning that the social attitude of the students was B (good). (2) spiritual attitudes get good results where as many as 75% of students score above 75% (3) for their learning outcomes, namely 52% have reached the minimum competency criteria (kkm) while the rest are not yet complete or have not reached kkm.